Analisis Kekasaran Dan Kapasitas Penampang Sungai Galang-Galang Kabupaten Polewali Mandar - Greistin Anggiani; Benyamin Tanan; Herman Welem Tanje (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Galang-Galang River or Binanga Karaeng River is a research site where this river is a border river between polewali mandar regency and Pinrang regency. In April 2020 there was a flood that damaged irrigation buildings on the right side of the bend downstream of the Galang-Galang River. This research aims to analyze the roughness and cross-sectional capacity of the Galang-Galang River. The data used consists of primary data and secondary data. The methods used in survey methods and location points are determined based on observation points that can represent the upstream, middle, and downstream sections. Analysis of roughness coefficients using manning equations. The coefficient of the galang-galang river upstream is 0.037, the middle is 0.015, and the downstream is 0.037. The difference in the coefficient value of roughness is influenced by cross-sectional irregularities, the size of the sediment grains that differ from each point, and the narrowing of the channel. Cross-sectional capacity in segments 1-1, 2-2, and 3-3 is unable to accommodate Q50 and Q100 flood discharges.